Peningkatan Pengetahuan Wanita Warga Binaan Lapas Kelas IIB Padang Sidempuan Tentang Kanker Payudara Wanita Usia Subur: Peningkatan Pengetahuan Wanita Warga Binaan Lapas Kelas IIB Padang Sidempuan Tentang Kanker Payudara Wanita Usia Subur - Harahap, Irawati; Harahap, Nur Hamimah; Nasution, Nur Arfah; Mutia, Fatma; Mulia, Diana (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Education and introduction about breast cancer is very important to reduce new cases through PKM (Community Service) outreach, increasing knowledge about the importance of recognizing the symptoms and impacts of breast cancer. The outreach activity aims to educate female residents of the class IIB Padang Sidimpuan prison about increasing knowledge of breast cancer. This activity will be carried out in December 2023 at the class IIB Padang Sidempuan prison. Carrying out activities for women inmates at the IIB prison providing PKM counseling by providing material (counseling) about breast cancer and BSE methods, then being taught awareness techniques and in the next stage, it is necessary to carry out breast examinations using a chest X-ray: to find out whether the cancer has spread to the lungs Bone scan: to find out whether the cancer has spread to the bones CT scan (computed tomography) MRI (magnetic resonance imaging) Ultrasound and mammography PET scan (positron emission tomography). One of the factors that triggers an increase in the incidence of breast cancer is the delay in early detection of breast cancer. The cause of delays in carrying out early detection is due to low knowledge and lack of education regarding how to detect breast cancer early. Early detection is the most effective way to reduce the death rate for breast cancer sufferers, namely by 25-30% and through early detection, the presence of cancer cells is known more quickly, so that appropriate therapy can be given to breast cancer sufferers.